Pengaruh Kualitas Produk, Fitur Produk, Lokasi Terhadap Kepuasan Nasabah Automathic Teller Machine (ATM) Bank Syariah Indonesia (BSI) Kantor Cabang Pembatu (KCP) Pangkalan Kerinci - Yuliana Marlisa Norhijar; Ainun Mardiah (Al-Manar Journal of Public Administration and Management, 2024)
The purpose of this research is to determine the effect of product quality (X1) product features (X2) and location (X3) on customer satisfaction (Y) at Bank Syariah Indonesia (BSI) Sub-Branch Office (KCP) Pangkalan Kerinci, both partially and individually. simultaneous. The population in this study were all customers who used the Automatic Teller Machine (ATM) of Bank Syariah Indonesia (BSI) Sub-Branch Office (KCP) Pangkalan Kerinci, totaling 100 people. The sampling method in this research used accidental sampling. The data used are primary and secondary data. The data analysis method in this research is quantitative using multiple linear regression tests and the data is analyzed using the SPSS program. The research results show that the variables product quality,product features and location affect customer satisfaction both partially and simultaneously. The result of the coefficient of determination is 0.643, shows that the product quality, product features and location as a whole have an influence of 64.3% on customer satisfaction.